INFORMATION ON DIGITAL MEDIA ETHICS, REGULATIONS AND POLICIES - Santi, Triana; Sazali, Hasan (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Rapid digital transformation has brought about fundamental changes in the way information is disseminated and consumed by society. The development of digital media not only offers easy access and speed of information distribution, but also raises serious challenges in the realm of ethics, regulation, and policy. This study aims to deeply analyze the role and challenges of information in the context of digital ethics, media regulation, and policies relevant to the current technological era. The method used is a qualitative approach, by conducting in-depth interviews with digital media experts. This study is also complemented by a review of the latest literature and case study analysis. The results of the study show that although digital media supports the democratization of information, it also opens up gaps for the spread of disinformation, hate speech, privacy violations, and inequality of access to technology. Analysis of public interest theory, deontology, cyberspace, and diffusion of innovation is used to understand the complexity of these challenges. These theories underline the importance of adaptive regulation, universal ethics, and collective responsibility in maintaining the digital information ecosystem. One important finding is the central role of digital literacy in helping people navigate online content ethically and critically. The conclusion of this study states that digital information management requires a multidisciplinary approach involving the government, platform providers, academics, and the general public. Effective policies must not only be repressive against violations, but also promotive in encouraging digital literacy and ethical awareness.